cytoNet: Spatiotemporal network analysis of cell communities. - Arun S Mahadevan; Byron L Long; Chenyue W Hu; David T Ryan; Nicolas E Grandel; George L Britton; Marisol Bustos; Maria A Gonzalez Porras; Katerina Stojkova; Andrew Ligeralde; Hyeonwi Son; John Shannonhouse; et al. (PLoS Computational Biology)
We introduce cytoNet, a cloud-based tool to characterize cell populations from microscopy images. cytoNet quantifies spatial topology and functional relationships in cell communities using principles of network science. Capturing multicellular dynamics through graph features, cytoNet also evaluates the effect of cell-cell interactions on individual cell phenotypes. We demonstrate cytoNet's capabilities in four case studies: 1) characterizing the temporal dynamics of neural progenitor cell communities during neural differentiation, 2) identifying communities of pain-sensing neurons in vivo, 3) capturing the effect of cell community on endothelial cell morphology, and 4) investigating the effect of laminin α4 on perivascular niches in adipose tissue. The analytical framework introduced here can be used to study the dynamics of complex cell communities in a quantitative manner, leading to a deeper understanding of environmental effects on cellular behavior. The versatile, cloud-based format of cytoNet makes the image analysis framework accessible to researchers across domains.